2011
DOI: 10.2174/138161211795164112
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Alzheimer's Disease: Rational Basis in Ongoing Clinical Trials

Abstract: Amyloid-β (Aβ) immunotherapy has recently begun to gain considerable attention as a potentially promising therapeutic approach to reducing the levels of Aβ in the Central Nervous System (CNS) of patients with Alzheimer's Disease (AD). Despite extensive preclinical evidence showing that immunization with Aβ(1-42) peptide can prevent or reverse the development of the neuropathological hallmarks of AD, in 2002, the clinical trial of AN-1792, the first trial involving an AD vaccine, was discontinued at Phase II wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 0 publications
1
43
0
Order By: Relevance
“…Importantly, immunization with SEDI peptide directed a Th2-biased immune response, which promotes antibody production and suppresses the Th1-type proinflammatory response. Of note, it was a Th1 immune response that led to meningoencephalitis in a subset of patients receiving immunizations of A␤ peptide in the AN1792 clinical trial for Alzheimer's disease (for review, see -González et al, 2011). Interestingly, Urushitani and colleagues (Takeuchi et al, 2010) have shown that immunization with WT-apo SOD1 induces a higher Th2/Th1 milieu than G93A-apo SOD1 vaccination, indicating the importance of antigen selection in obtaining the desired outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, immunization with SEDI peptide directed a Th2-biased immune response, which promotes antibody production and suppresses the Th1-type proinflammatory response. Of note, it was a Th1 immune response that led to meningoencephalitis in a subset of patients receiving immunizations of A␤ peptide in the AN1792 clinical trial for Alzheimer's disease (for review, see -González et al, 2011). Interestingly, Urushitani and colleagues (Takeuchi et al, 2010) have shown that immunization with WT-apo SOD1 induces a higher Th2/Th1 milieu than G93A-apo SOD1 vaccination, indicating the importance of antigen selection in obtaining the desired outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although adequate preclinical data accentuated that immunization with Ab(1-42) peptide ameliorates disease symptoms by curtailing the development of the neuropathological hallmarks of AD in 2002 yet the first clinical trial of AN-1792 AD vaccine was terminated at Phase II due to the development of meningoencephalitis in patients [20]. Further, anti-Ab monoclonal antibodies Bapineuzumab, Solanezumab also failed to show neuroprotective effect in phase III clinical trials of AD in turn inducing side effects such as meningoencephalitis, vasogenic edema in patients [118].…”
Section: Preclinical Versus Clinical Studiesmentioning
confidence: 99%
“…Despite the significant improvement in research related to apoptotic mechanisms there is no substantial therapeutic strategy to stop or slow this process. Additionally, there exists a considerable ambiguity between several preclinical and clinical studies with respect to disease mechanism and therapeutic strategies [19,20]. Therefore, this review throws light on various apoptotic mechanisms and the possible therapeutic avenues for AD.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the initially severe adverse effects observed in humans [33,34], further studies focused on the design of effective and safe immunotherapy [35,36]. One of these immunotherapies, based on a mixture of fibrillar Aβ components, has been developed in our laboratory with great effectiveness and complete safety in domestic dogs with CDS [37].…”
Section: Introductionmentioning
confidence: 99%